2017
DOI: 10.3747/pdi.2016.00109
|View full text |Cite
|
Sign up to set email alerts
|

Significant Decreasing Incidence of Encapsulating Peritoneal Sclerosis in the Dutch Population of Peritoneal Dialysis Patients

Abstract: The Dutch Encapsulating Peritoneal Sclerosis (EPS) Registry was started in 2009. Cases were identified by contacting all Dutch nephrologists twice yearly. The predefined criteria for EPS allowed for inclusion of patients with diagnosed and suspected EPS. Cases registered between January 2009 and January 2015 were analyzed with follow-up until September 2015. Fifty-three EPS cases were identified, of which 28.3% were post-transplantation EPS cases. Fourteen patients were initially categorized as suspected EPS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…Genetic variation in the receptor for AGEs might predispose to peritoneal deterioration [92]. Mortality approaches about 50% at 1 year after diagnosis of EPS in PD patients [90,93]. The rarity of the disorder, its variable presentation, and the lack of screening tools frequently lead to diagnosis being delayed.…”
Section: Encapsulating Peritoneal Sclerosismentioning
confidence: 99%
“…Genetic variation in the receptor for AGEs might predispose to peritoneal deterioration [92]. Mortality approaches about 50% at 1 year after diagnosis of EPS in PD patients [90,93]. The rarity of the disorder, its variable presentation, and the lack of screening tools frequently lead to diagnosis being delayed.…”
Section: Encapsulating Peritoneal Sclerosismentioning
confidence: 99%
“…Promisingly, the annual incidence of EPS is decreasing. A Dutch study reported a remarkable decrease in the annual incidence of EPS from 0.85% in 2009 to 0.14% in 2014 [22]. This decrease can be attributed to advances of PD techniques, use of physiological PD solutions (e.g., neutral solutions with low glucose degradation products), and availability of expert training to prevent peritonitis [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In EPS management, developing a systemized protocol to detect and treat EPS in the early phase is important [25]. Tamoxifen with or without steroids in the early phase of EPS could be beneficial for inhibiting progression to severe EPS or recurrence [22,26].…”
Section: Discussionmentioning
confidence: 99%
“…Around the globe centres reported a variable incidence ranging between 0.8 and 19.4% which may be increasing along with the PD duration (22,24). A recent Dutch study showed a decrease in incidence from 0.85 in 2009 to 0.14 in 2014 without a decrease number of patients on PD (25).…”
Section: Discussionmentioning
confidence: 99%